Synthesis of environment-friendly (Bi, Ca, Zn)VO4 inorganic yellow pigments - Tuyen, Tran Ngoc; Quyen, Nguyen Duc Vu; Hai, Ho Van Minh; Tin, Dang Xuan; Mai, Dao Thi Phuong (Vietnam Journal of Science and Technology, 2017)
In this paper, the synthesis of scheelite based environmentally friendly inorganic yellow pigments was presented. The pigments of Bi1-x-yCaxZnyVO4-(x+y)/2 (x = 0.1 ÷ 0.9, y = 0.1 ÷ 0.9) have been prepared by the evaporation to dryness from BiONO3, Ca(NO3)2.4H2O, Zn(NO3)2.6H2O and NH4VO3. The obtained powders were characterized by Thermal Analysis (TG-DSC), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and CIE L*a*b* colour measurement. The results showed that the pigments calcinated at 650oC for 6 hours with the heating rate of 5oC.min-1 possessed single phase of scheelite with good crystallinity. The yellow colour intensity was a function of the amount of calcium (II) and zinc (II) ions. The colour of Bi0.70Zn0.30VO3.85 sample was similar to the lemon yellow PbCrO4 (BASF1522) pigment made by Hangzhou Emperor Pigment Company (China).